Determinants of Customer Satisfaction in Regional Culinary Businesses: Examining the Moderating Roles of Product Quality and Accessibility - Meista Bambang Wahyu Saputri; Nur Hidayati; Supriyanto (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the influence of facilities and infrastructure as well as location on customer satisfaction, with product quality and accessibility as moderating variables at Pondok Rumbia Restaurant, Sulawesi. Using a quantitative explanatory approach, data were collected from 100 customers through accidental sampling and analyzed using Partial Least Squares (PLS). The results reveal that facilities and infrastructure have a positive and significant effect on customer satisfaction, while location does not show a significant direct effect. Product quality significantly moderates the relationship between facilities and infrastructure and customer satisfaction, and accessibility moderates the relationship between location and customer satisfaction. These findings suggest that customer satisfaction is primarily driven by the quality of facilities, which is further strengthened by product quality and accessibility. Therefore, restaurant managers should integrate improvements in facilities, product quality, and ease of access to enhance overall customer satisfaction.